PENYELENGGARAAN BANK DIGITAL DITINJAU DARI HUKUM PERBANKAN DI INDONESIA - Felicia (2022)
Digital banking has emerged as an innovation in banking operations so that banks in Indonesia can achieve their goals to improve the progress of the nation. As something new, digital banking still poses many big questions for the public. Therefore, this paper attempts to explain digital banking with the following problem formulation: (1) What is the legality of implementing Digital Banks in Indonesia? (2) How is the implementation of digital banking fulfilling the principles of banking law by positive Indonesian law? This normative research uses a statutory problem approach with the primary data source being legislation related to banking. Regulations regarding digital banks are specifically contained in POJK Number 12/Pojk.03/2018 concerning the Implementation of Digital Banking Services by Commercial Banks. In carrying out their activities digital banks also have several problems and challenges, therefore digital banks must apply banking legal principles like traditional banks in general, previous regulations regarding digital banking services must be used in implementing banking legal principles in digital banks because there are no regulations governing this matter. Keywords: legality, digital bank, banking legal principles, POJK